Synopsis: Women’s empowerment in Rwandan agriculture: A baseline assessment in the context of Rwanda’s gender and youth mainstreaming strategy and the fourth strategic plan for agricultural transformation - Rosenbach, Gracie; Benimana, Gilberthe Uwera; Ingabire, Chantal; Spielman, David J.; Tumukunde, Ritha (International Food Policy Research Institute, 2023)
Rwanda is a recognized leader in the region and the world in terms of women’s empowerment. However, no country has yet achieved full gender equality, resulting in untapped potential for improvement. The findings from the Women’s Empowerment in Agriculture Index (WEAI) baseline survey conducted in 2019 for the Ministry of Agriculture and Animal Resources (MINAGRI) indicate that women and men in Rwanda have both relatively high levels of empowerment across different agricultural domains, while many women are as empowered as men in their households, some gender disparities remain.